2017
DOI: 10.1002/joec.12066
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes of Planned Happenstance Skills by Gender, Community Types, and Employment Status in a Sample of College Students in School‐to‐Work Transition

Abstract: This study examined the characteristics of college students who are transitioning from school to work by measuring their mean differences on planned happenstance skills subscales at 3 separate time points. The results indicated that the mean of planned happenstance skills changed across the 3 time points and are somewhat different through demographic factors, such as gender, community types, and employment status. In addition, 2‐way and 3‐way multivariate analysis of variance results showed that the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…Based on the decrease in PHS scores these authors suggested that academic advisors may opt use of the PHCI in a counseling context (Yang et al, 2017). In a longitudinal study, Kim et al (2017) found during this transitory period, a similar decrease in these aforementioned PHS scores with particular emphasis on the persistence. Furthermore, PHCI skill scores are confirmed to have associative relationships with differential measures of career-related variables such as career aspiration, career barriers, career engagement, and career decision self-efficacy and theoretical models postulate how PHS intersect with these variables (Kim et al, 2014a(Kim et al, ,b, 2015(Kim et al, , 2016Rhee et al, 2016;Kim et al, 2017;Yang et al, 2017).…”
Section: The Clinical Anatomy Graduate Program At Western Universitymentioning
confidence: 93%
See 2 more Smart Citations
“…Based on the decrease in PHS scores these authors suggested that academic advisors may opt use of the PHCI in a counseling context (Yang et al, 2017). In a longitudinal study, Kim et al (2017) found during this transitory period, a similar decrease in these aforementioned PHS scores with particular emphasis on the persistence. Furthermore, PHCI skill scores are confirmed to have associative relationships with differential measures of career-related variables such as career aspiration, career barriers, career engagement, and career decision self-efficacy and theoretical models postulate how PHS intersect with these variables (Kim et al, 2014a(Kim et al, ,b, 2015(Kim et al, , 2016Rhee et al, 2016;Kim et al, 2017;Yang et al, 2017).…”
Section: The Clinical Anatomy Graduate Program At Western Universitymentioning
confidence: 93%
“…Using Qualtrics online survey software (Qualtrics, Provo, UT), the PHCI was distributed to participants after the interviews. It assesses PHSs through a series of five-point Likert scale questions (1 = strongly disagree, 2 = disagree, 3 = neutral, 4 = agree, 5 = strongly agree) (Table 1) (Kim et al, 2014b(Kim et al, , 2017. Each of the five skills have five sub-questions used to determine a skill value.…”
Section: Quantitative Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Salah satu faktor internal yang ditemukan memengaruhi CDSE secara signifikan adalah keterampilan memanfaatkan kejadian tak terduga sebagai peluang (Krumboltz, 2009). Hal ini disebut sebagai planned happenstance, yang didefinisikan sebagai keterampilan dan kemampuan individu untuk menangkap kejadian tak terduga sebagai peluang (Kim, Kim, Yang, Yaung, & Lee, 2017). Krumboltz (2009) menyatakan bahwa orang tua memiliki peranan yang krusial dalam membentuk keterampilan planned happenstance ini.…”
Section: Pendahuluanunclassified
“…Atas dasar teori pembelajaran kebetulan Krumboltz, Mitchell et al (1999) mengusulkan happenstance skill, yaitu : (a) keingintahuan (curiousity), memeriksa peristiwa untuk pembelajaran baru atau kesempatan belajar baru; (b) kegigihan (persistance), gigih melanjutkan pengalaman belajar baru meskipun mengalami kemunduran; (c) fleksibilitas (flexibility), mengubah keterampilan melintasi keadaan yang ada atau tetap menghadapi kondisi walaupun tidak ideal; (d) optimis (optimism), melihat keyakinan bahwa suatu peristiwa yang terjadi sebagai pengalaman belajar; dan (e) berani mengambil risiko (risk taking), mengambil tindakan saat dihadapkan dengan peristiwa yang tidak direncanakan atau hasil yang tidak pasti. (Kim, Kim, Yang, Yaung, & Lee, 2017). Dalam penelitian yang dilakukan oleh Boyoung Kim, menunjukkan bahwa toleransi atau keterbukaan seseorang pada kejadian tidak terduga menjadi hal yang penting dalam membangun kepercayaan diri dalam memilih karir (Kim, Rhee, Ha, Yang, & Lee, 2016).…”
Section: Planned Happenstance Skillunclassified